Global Perspectives of Oral Health Policies and Oral Healthcare Schemes for Older Adult Populations - Jiang, Chloe Meng; Chu, Chun Hung; Duangthip, Duangporn; Ettinger, Ronald L.; Hugo, Fernando Neves; Kettratad-Pruksapong, Matana; Liu, Jian; Marchini, Leonardo; McKenna, Gerry; Ono, Takahiro; Rong, Wensheng; Schimmel, Martin; et al. (Frontiers in Oral Health, 2021)
The aim of this study was to present a concise summary of the oral health policies and oral healthcare schemes for older adult populations in a number of selected countries around the world. In this paper, the current and planned national/regional oral health policies and oral healthcare schemes of nine countries (Australia, Brazil, China including Hong Kong, India, Japan, Switzerland, Thailand, the United Kingdom, and the United States) are reported. Barriers and challenges in oral health promotion in terms of devising oral health policies, implementing oral health schemes, and educating the future dental workforce are discussed. In response to the aging of population, individual countries have initiated or reformed their healthcare systems and developed innovative approaches to deliver oral health services for older adults. There is a global shortage of dentists trained in geriatric dentistry. In many countries, geriatric dentistry is not formally recognized as a specialty. Education and training in geriatric dentistry is needed to produce responsive and competent dental professionals to serve the increasing number of older adults. It is expected that oral health policies and oral healthcare services will be changing and reforming in the coming decades to tackle the enduring oral health challenges of aging societies worldwide.